Kemampuan Mahasiswa Calon Guru Matematika dalam Membuat Soal Tipe Pemecahan Masalah Kontekstual (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to determine the ability of preservice mathematics teachers to make contextual problem-solving type questions and their problems. This research is descriptive qualitative research. The research subjects were eight prospective mathematics teacher students who had received courses in mathematics learning planning, mathematics learning strategies, evaluation of mathematics learning,  and had carried out teaching practice programmes. Research subjects are asked to make a question and its solution with the basic competencies that have been determined. The results showed that attention is still needed in making contextual problem-solving type questions for preservice mathematics teachers, because there are problems found in some preservice teachers,, namely: 1) the resulting solutions were not logical, 2) the questions arranged were not in accordance with the basic competencies, even though the material was the same, 3) the questions cannot be solved because the information on the questions is incomplete, 4) the questions include routine questions and only 1 step of completion, and the most common is 5) in composing ambiguous question sentences so that it can lead to different interpretations between question makers and students.
Keywords: make questions; contextual problem solving; preservice teacher skills